2018
DOI: 10.1080/15321819.2018.1509871
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Th1 and Th2 cytokine serum levels and immune response to Hepatitis B vaccination among Egyptian health care workers

Abstract: Hepatitis B virus (HBV) vaccination leads to both humoral and cellular immune responses and results in protecting levels of specific antibodies. The immune response to the vaccine and production of T-helper 1 (Th1) and Th2 cytokines vary among the individuals. Thus we aimed to investigate the relationship between Th1/Th2 cytokine serum levels and antibody production after HBV vaccination, hoping to improve the effectiveness of vaccination. A total of 90 health care workers had been vaccinated with triple doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…It can be speculated that sCD30 may be more related to nonresponsiveness rather than responsiveness. Although some studies have reported inadequacy of Th1 and Th2 cytokines in non-responders, Larsen et al have reported that poor responders produce primarily Th2 cytokines similar to our results [22,26] . These different results may depend on different technical methods (in vivo and in vitro cytokine measurement) and the demographics of the study groups, but may also be interpreted as sCD30 plays an essential role in the balance of Th1/Th2 response rather than being a marker of Th2 considering all of the mentioned studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It can be speculated that sCD30 may be more related to nonresponsiveness rather than responsiveness. Although some studies have reported inadequacy of Th1 and Th2 cytokines in non-responders, Larsen et al have reported that poor responders produce primarily Th2 cytokines similar to our results [22,26] . These different results may depend on different technical methods (in vivo and in vitro cytokine measurement) and the demographics of the study groups, but may also be interpreted as sCD30 plays an essential role in the balance of Th1/Th2 response rather than being a marker of Th2 considering all of the mentioned studies.…”
Section: Discussionsupporting
confidence: 90%
“…Various factors affecting response to HBV vaccine, other than immunologic factors have been investigated to understand the ethiogenesis of non-responsiveness so far for enhancing the HBV vaccine efficacy [5] . Since esponse to HBV vaccine is related to antibody level, Th cells presenting HBsAg have been the most emphasized subjects [22] . Th cells are divided into Th1 and Th2 cells based on the types of secreted cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this theory, some studies have revealed that high responders to the HBV vaccine have significantly higher levels of Th1 cytokines, Il-2 and IFN-γ, and Th2 cytokines, Il-10 and Il-13, than did non-responders [46,47]. A recent study on participants vaccinated with HBV vaccines also reported that the levels of IFN-γ, a Th1 cytokine, and Il-13, a Th2 cytokine, are positively correlated with the anti-HBs titer [48]. Hence, the decrease in the levels of IFN-γ [17], Il-10, and Il-13 [18] observed upon the BPA treatment of human peripheral blood mononuclear cells indicate that BPA suppresses both Th1-and Th2-type immune responses for antibody formation, resulting in low anti-HBs titers.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of hepatitis B is an inflammation mediated by immune over-expression, mainly the imbalance between Thl/Th2 [9,10]. The damage of hepatic tissue is due to the immune system being sensitized by HBV, which stimulates the immune system, participates in host immune defense response, and produces corresponding antibodies and/or cellular non-specific immune response [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%